Building up Undergraduate Skills – empirical evidence from a Portuguese University - Oliveira, Eva (2018)
This study presents preliminary results of the PSP Project, addressing students‟ soft skills development within the context of HEI. Theoretical framework is grounded in Person-Environment Fit theories (Rounds & Hesketh, 1994), and also in Evans (2001) starfish model. Study 1 aimed to identify Economics and Business graduates‟ Market-Valued Skills Profile, collecting data through semi-structured interviews with HR managers and former students focus groups. Study 2 assessed students‟ confidence level regarding skills using a self-report questionnaire (Miles & Grummon, 2006). Career development representations were also assessed (Savickas, 2002; Gonçalves, 2006). Additional data was collected through open-ended questions focusing on work and other extracurricular experiences. Results from Study 1 highlight soft skills as multidimensional construct where different interrelated skills contribute to graduates‟ employability. Study 2 reveals students‟ positive self-perception regarding those skills, although limited vocational experiences were reported.